Host influence on the nutritional and reproductive status of Triatoma infestans (Klug) (Hemiptera: Reduviidae) peridomiciliary populations - Soria, Carola (2019)
Triatoma infestans is the main vector of Chagas disease in the southern cone of South America. This species is well adapted to living in rural houses and structures used for housing domestic animals (peridomestic habitats). In this study, we evaluated the relationship between the source of blood consumed by adults of T. infestans collected from different peridomestic habitats from two localities from Cruz del Eje department (Córdoba, Argentina) and their nutritional and reproductive status. In each individual, the ratio between body weight and total body length was used as an indicator of nutritional status (NS). The presence of sperm in spermathecae and the number of chorionated oocytes in ovaries and oviducts were considered indicators of reproductive status (RS) of females. The feeding source in the promesenteron of male and female insects was identified using anti-chicken, anti-goat, antihuman and anti-dog antisera. Chicken coops were the main peridomestic structure present in the study area as well as the peridomestic sites with the highest percentage of T. infestans. Insects collected from the different peridomestic structures showed a NS between 8 and 15 mg/mm. Of the evaluated females, 35.7% presented chorionated oocytes. Food profile analyses revealed that chicken was the main blood source. Independently of the blood source, the triatomines presented a NS between 8 and 15 mg/mm. No specimens feeding exclusively on human blood were found; nevertheless, of 31.48% of insects feeding on mixed blood sources, 59% included human blood. All T. infestans specimens that included human blood in the mixed blood source were collected from chicken coops and storerooms located in a 12-m area around domiciles. Human blood present in mixed blood meal of adult insects suggests that T. infestans moves from domiciles to peridomicilies and vice versa.